2013
DOI: 10.7726/ajafst.2013.1001
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin Decreases Inflammatory Biomarkers Associated with Cardiovascular Disease in Human Umbilical Vein Endothelial Cells

Abstract: Oxidative stress and inflammation are strongly linked to the development of cardiovascular disease (CVD). As a potent antioxidant, astaxanthin may downregulate inflammation-associated factors involved in endothelial dysfunction and CVD progression. We studied the possible protective effects of astaxanthin against endothelial dysfunction in human umbilical vein endothelial cells (HUVEC) induced with hydrogen peroxide (H2O2). Cells were pre-incubated with 0, 0.01, 0.1, or 1.0 μmol/L astaxanthin for 48 h, then ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 25 publications
2
14
0
1
Order By: Relevance
“…Oxidative stress is a main cause of cellular damage in several diseases, including xerostomia [40,41]. In addition to therapeutic interventions, bioactive compounds with antioxidant activity have been reported to be capable of protecting cells from oxidative stress [42,43]. The bioactive compound cordycepin has been previously reported to be effective against oxidative and endoplasmic reticulum stress by reducing intracellular ROS generation in vitro [15,44].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is a main cause of cellular damage in several diseases, including xerostomia [40,41]. In addition to therapeutic interventions, bioactive compounds with antioxidant activity have been reported to be capable of protecting cells from oxidative stress [42,43]. The bioactive compound cordycepin has been previously reported to be effective against oxidative and endoplasmic reticulum stress by reducing intracellular ROS generation in vitro [15,44].…”
Section: Discussionmentioning
confidence: 99%
“…This results in low permeabilization into cells and thus few studies have been conducted on its effects. However, Chew et al (26) found that astaxanthin does slowly permeate into cells, with a peak at 24-48 h, and thus may be a treatment candidate. In this study, H 2 O 2 was used to induce oxidative damage and astaxanthin treatment for 48 h was shown to effectively relieve H 2 O 2 -induced endothelial cell death, reduce the production of active oxygen, and protect the MMP.…”
Section: Discussionmentioning
confidence: 99%
“…The consistency of these results points to assign a remarkable potential to astaxanthin as a bioactive compound that may decrease the risk of developing adverse diseases including cancer [ 67 ], gastric ulcers by Helicobacter pylori [ 75 ] and other gastrointestinal disorders [ 76 , 77 ]. Some studies claim the positive influence of astaxanthin in the gastrointestinal health [ 70 , 78 ] and as a therapeutic agent against cardiovascular disease [ 79 , 80 , 81 , 82 ]. The antioxidant activity of astaxanthin presents other collateral benefits in the enhancement of the immune system as it has been shown by in vitro and in vivo experimental animal models [ 65 ] and humans [ 83 ].…”
Section: Bioaccessibility Of Astaxanthinmentioning
confidence: 99%